Performance Evaluation of Ginger Genotypes on their Yield and Nutrient Uptake under the Coastal Karnataka, India - Y., Ravi; V. B, Narayanpur; P. M., Gangadharappa; J. S, Hiremath; T., Shantappa; A., Prashant; M. B, Doddamani (International Journal of Bio-resource and Stress Management, 2022)
A field experiment was conducted during kharif (June, 2014–January, 2015) at College of Horticulture, Sirsi, Karnataka, India to study the yield, yield attributing traits, nutrient content and nutrient uptake pattern in ginger genotypes. In the present study 16 ginger genotypes including nationally released varieties viz. IISR-Mahima, IISR-Varada, IISR-Rajatha, Suravi, Suprabha, Himagiri, Rio-de-Janeiro, Suruchi, Himachal, Karkal Local, Humanabad Local, Jorhat-1, Jorhat-2, Bidar-1, Bidar-2 and Shikaripura Local were selected with an aim to assess the yield performance of selected genotypes and varieties in order to determine nutrient content and absorption pattern. Research results indicate that among 16 ginger genotypes including national released varieties the genotype Humnabad Local has recorded maximum number of primary rhizomes (6.30) and secondary rhizomes (24.50), higher fresh rhizome yield (360.20 g plant-1) and yield per hectare (21.55 t ha-1), dry recovery (27.35%). The genotype Bidar-1 recorded highest nitrogen content in rhizome (1.49%), whereas the variety IISR-Mahima recoded highest nitrogen content in root (1.16%) and in shoot (1.60%). Genotype Shikaripura local recorded maximum phosphorus content in rhizome (0.41%), root (0.39%) and in shoot (0.59%). Genotype Humnabad Local recorded highest potassium content in root (2.57%), whereas the variety IISR-Mahima recorded highest potassium content in rhizome (2.58%) and shoot (2.56%). The nutrient uptake pattern of ginger genotypes indicates that the ginger crop is potassium and nitrogen exhaustive. The results of this study provide a guideline for fertilizer application to ginger crop with respect to varieties, quantity and proportion of nutrient elements according to the demand of variety.